Evaluation of Ascophyllum nodosum extract supplementation on feed degradability, ruminal fermentation and methane production using the rumen simulation technique (RUSITEC) - Aaron Casey; Tommy M. Boland; Alan K. Kelly; Zoe C. McKay; Maria Markiewicz-Keszycka; Armin Mirzapour-Koudash; Marco Garcia-Vaquero; Sivaprakash Balakrishnan; Kieran J. Guinan; John T. O’Sullivan; Stafford Vigors (PLoS ONE, 2026)
This study investigated the effects of liquid Ascophyllum nodosum (ASC) extracts on feed degradability, ruminal fermentation, total gas and methane (CH 4 ) production using the rumen simulation technique (RUSITEC). Two experiments were conducted: Experiment 1 assessed a grass-based diet with an ASC extract included at 0.1%, 0.2% and 0.3% of dry matter (DM), while Experiment 2 evaluated a grass silage-based diet with an ASC extract included at 0.3%, 0.4% and 0.5% of DM. Both diets included a control treatment (CTR; no seaweed extract). In Experiment 1, the 0.3% treatment reduced CH 4 production relative to CTR, primarily by decreasing nutrient degradation and total volatile fatty acid production, resulting in reductions of 20% for total gas, 34% for CH 4 (mmol/d) and 30% for CH 4 (mmol/g of digestible organic matter; DOM). Metabolic hydrogen produced and incorporated were also reduced. In Experiment 2, the 0.5% treatment decreased DM and organic matter degradation compared to CTR, with no effects on crude protein or neutral detergent fibre degradation, or rumen fermentation parameters. Despite this, all ASC extract treatments reduced total gas by 20–24%, CH 4 (mmol/d) by 23–26% and CH 4 (mmol/g DOM) by 21–29% relative to CTR. Metabolic hydrogen recovery decreased by 22% across all ASC extract treatments, suggesting other mechanisms were at play redirecting hydrogen away from methanogenesis. These findings highlight the potential of ASC extract as a natural CH 4 -mitigating feed additive under controlled fermentation conditions, supporting the development of more sustainable ruminant production systems.